Appraisal of biological activities of crude extracts with sub-fractions and phytochemical content of endemic Nepeta nuda L. subsp. lydiea from Turkey - Geçibesler, İbrahim Halil and Kiliç, Ömer and Demirtaş, İbrahim (Progress in Nutrition, 2017)
Antioxidant activity of crude water extract (CWE) of this plant and its five sub-fractions (namely, hexane fraction (HF), chloroform fraction (CFF), ethyl acetate fraction (EAF), n-butyl alcohol fraction (BAF) and rest of the fractions (RF) were measured using in vitro two antioxidant assays: DPPH and ferrous ion chelating. Also, quantitative content of total flavonoids and phenols were carried out by colorimetric methods, using aluminum chloride method and Folin Ciocalteu reagent respectively. CWE and five sub-fractions possessed different antioxidant activities in antioxidant assays. EAF showed the most potent activity on DPPH radicals and ferrous ion chelating activities with IC50 values of 10.45 and 16.76 µg /ml respectively. EAF had the highest total phenolics (145.06 µg GAE/mg dried extract or fraction) and total flavonoids (50.16 µg QEE/mg dried extract or fraction) contents. The essential oil of the aerial parts of this plant was analyzed by headspace gas chromatography mass spectroscopy (HS-GC/MS) for the first time and fifty nine components were identified representing 95.91% essential oil. 1,8-cineole (28.79%), nepetalactone (9.93%), sabinene (7.88%) and α-pinene (5.71%) were identified as the major components. The essential oil analyzes results have given some clues on the commercial usable, renewable resources and potentials usable of the Nepeta taxa.